(untitled) (Architecture Image Studies, 2025)
Morocco’s National Education, Preschool and Sports sector is following the trend of improvement observed in other areas, with a positive progression in the rate of feminization among teaching staff, particularly in physical education and sports. However, it is regrettable to note that this progress is not reflected at the same level within decision-making, direction, and inspection positions. Regrettably, the proportion of women in senior management positions remains limited within this sector.The aim of this article is to examine the determinants of the formation of the glass ceiling among women teachers of physical education and sports, that is, the factors hindering the will of women teachers of physical education to advance in their career.To unveil the barriers impeding the progress of careers for women teachers in Physical and Sports Education (PSE), we have opted to conduct a comprehensive case study within a provincial directorate of National Education, Preschool Education, and Sports in Ain Choc. This directorate is a component of the largest National Education, Preschool Education, and Sports academy in Morocco, functioning under the purview of the pertinent ministry. The study is grounded in theoretical frameworks and empirical methods, incorporating questionnaires, participant observation, and secondary data analysis.As a result of our study, we have confirmed that women PES teachers are influenced by the following factors: gender, organization and the system. In fact, these different factors slow them down in their desire to advance in their career. The intensity of each factor differs from each other.Our article provides an original contribution to this research, considering the limited number of studies in this particular field. Nevertheless, it is constrained by the restricted sample size when it comes to generalizing the results.